Variability in Response of Groundnut (Arachis hypogaea L.) Genotypes to Moisture Stress and Stress Release - Sunitha, V.; Vanaja, M.; Sowmya, P.; Razak, S. K. Abdul; Kumar, G. Vijay; Anitha, Y.; Lakshmi, N. Jyothi (International Journal of Bio-resource and Stress Management, 2015)
Groundnut (Arachis hypogaea L.) is an important oilseed cash crop and an erratic rainfall with prolonged dry spells during critical pheno-phases of reproductive stages affects its yield. A field trial was carried out with groundnut genotypes- JL-24, ICGV 91114, Narayani, Abhaya, Dharani and Greeshma to study the variability in morphological, biochemical and yield traits to moisture stress at flowering stage. Significant reduction in growth and yield components of all the selected groundnut genotypes was observed due to moisture stress. ANOVA for pod weight, seed weight, 100 seed weight, harvest index, total biomass were found to be highly significant (p<0.01) for genotypes, moisture levels and their interactions. Impact of moisture stress on plant height, leaf area, leaf and shoot biomass was lowest in Dharani and osmoprotectant- proline and activity of antioxidant enzymes- SOD and POD were higher in Dharani. The yield performance of Narayani, Abhaya, Dharani were similar as well as superior under control condition where as under moisture stress conditions Dharani recorded highest seed yield, HI with lowest reduction in seed number and 100 seed weight. Under control conditions seed yield had significant positive correlation with pod number, pod weight and seed number whereas under moisture stress conditions with SOD, POD, leaf area, leaf dry weight, pod weight, seed number, 100 seed weight and shelling %. The groundnut genotype Dharani performed best under both control and moisture stress conditions as its high anti-oxidative enzyme activity and proline content might have been ameliorated the ill effects of moisture stress.